Flow analysis of water with aluminum oxide nanoparticles in a 90° bend pipe with injection using computational fluid dynamics - Mahdizadeh, Hadi (2018)
In several heat exchangers, the shape of the pipes is bent. Flow behavior in a curved tube is much more complex than straight pipes. Also, Nano-fluids are utilized in many industrial applications for increase thermal efficiency. Therefore, the aim of this study is investigation of the effect of injection into a 90° bend tube with A12O3 Nano-fluid. Computational fluid dynamics study of a flow through a bent tube of 90° via fluid injection was performed using ANSYS FLUENT software. Conservation equations of mass, momentum and energy are discretized using finite volume method. SIMPLE algorithms have been used to solve it. The effects of volume fraction of Nano-fluid, (0%, 2%, 4%, 6%) fluid injections number (0, 1, 2) and position of injection before and after bend have been investigated. Evaluation of best performance of mixing injection and bend in different positions and analyzing the effect of Nano-fluid volume fraction on injection is done for having most Nusselt number and lowest pressure drop in pipe. The results show that the using nanoparticles in bent tube increase the heat transfer performance by 8%. The results obtained show that increasing the volume fraction has a direct impact on decreasing the heat transfer. Even with increase of volume fraction from 2% to 6%, the Nusselt number decreased by 0.7%. By investigation of distance of two injections, the maximum heat transfer has obtained in the injection with distance of 2.5 times of pipe diameter. For study of position of injections and number of it, the geometry with one injection before the bend has the best heat transfer rate and the lowest pressure.